Temporary Modification to the Fund's Annual Access Limits. (Policy Papers; Policy Paper ;, 2020)
The COVID-19 pandemic has caused a uniquely severe synchronized shock across the global economy, in turn leading numerous member countries to request substantial financial assistance from the Fund. The Executive Board responded to members' needs by increasing the access limits under the Fund's emergency financing instruments by 50 percent of quota for a period of 6 months (until October 5, 2020), subject to a possible extension by the Executive Board.